The need to know: HIV status disclosure expectations and practices among non-HIV-positive gay and bisexual men in Australia - Murphy, Dean; De Wit, J.; Donohoe, S.; Adam, P. (Routledge, 2015)
Although there is evidence of increasing overall rates of HIV status disclosure among gay and bisexual men, little is known about men's disclosure expectations and practices. In this study, we investigate the importance non-HIV-positive men in Australia vest in knowing the HIV status of their sexual partners, and the extent to which they restrict sex to partners of the same HIV status, and their HIV disclosure expectations. Data were collected through a national, online self-report survey. Of the 1044 men included in the study, 914 were HIV negative and 130 were untested. Participants completed the assessment of socio-demographic characteristics, HIV status preferences, and disclosure expectations and practices. Participants also completed reliable multi-item measures of perceived risk of HIV transmission, expressed HIV-related stigma, and engagement with the gay community and the community of people living with HIV. A quarter (25.9%) of participants wanted to know the HIV status of all sexual partners, and one-third (37.2%) restricted sex to partners of similar HIV status. Three quarters (76.3%) expected HIV-positive partners to disclosure their HIV status before sex, compared to 41.6% who expected HIV-negative men to disclose their HIV status. Less than half (41.7%) of participants reported that they consistently disclosed their HIV status to sexual partners.Multivariate linear regression analysis identified various covariates of disclosure expectations and practices, in particular of disclosure expectations regarding HIV-positive men. Men who expected HIV-positive partners to disclose their HIV status before sex more often lived outside capital cities, were less educated, were less likely to identify as gay, perceived more risk of HIV transmission from a range of sexual practices, were less engaged with the community of people living with HIV, and expressed more stigma towards HIV-positive people. These findings suggest that an HIV-status divide is emerging or already exists among gay men in Australia. HIV-negative and untested men who are most likely to sexually exclude HIV-positive men are less connected to the HIV epidemic and less educated about HIV risk and prevention.